A strategic leadership framework for educational change - Bumatay, Ernesto L. (USM R & D Journal, 2009)
The paper develop a strategic leadership (SL) framework for internal and external educational reforms for higher learning institutions. It attempts to understand the best strategic variables for leadership from the perspectives of selected university presidents locally and in the Asian region. The proposed SL framework has four mutually exclusive quadrants: Q1 - the "educational leader" (higher education leader), Q2 - the "entrepreneurial perspectives and environment" (creative and innovative environment), Q3 - the" paradoxical leadership' (strategic leadership) and Q4 - the "Strategic perspectives and results" (strategic thinking and process perspectives).